Anti‐jamming method for STAP based on a bi‐phase random‐coded signal. Issue 19 (25th July 2019) - Ye, Weijie; Yang, Xiaopeng; Sun, Yuze; Li, Shuai
Abstract : The scattered‐wave sweeping frequency jamming occupies many space‐time adaptive processing (STAP) degrees of freedom, which results in a serious decline in STAP performance. To solve this problem, an anti‐jamming method of STAP based on a bi‐phase random‐coded signal is proposed. This method utilises the phase‐coded signal's ability of waveform agile and anti‐jamming. Also, the phase coding is designed as a random sequence, which distinguishes and suppresses the interference by white noise characteristic. Simulation results show that, compared with the STAP method based on a chirp signal, the proposed method improves beamforming robustness and clutter suppression capability under an interfering background.